The Effect of Love of Money on Tax Fraud with Gender and Religiosity as Moderating Variables - Kurniawan, Shintyaa Oktaviana; Pontoh, Grace T.; Ferdiansah, Muhammad Irdam (Jurnal Manajemen Bisnis, Akuntansi dan Keuangan, 2024)
The aim of this research is to test and analyze the influence of love of money on tax fraud with gender and religiosity as moderators at the North Makassar Primary Tax Service Office. This research data uses primary data obtained from questionnaires distributed to all 104 KPP Pratama North Makassar employees. Data analysis was carried out using Partial Least Squares (PLS) 3.0. The research results show that love of money has a significant and positive effect on tax fraud and gender strengthens and religiosity weakens the influence of love of money on tax fraud. This indicates that the high love of money and the support of gender factors cause taxpayers to commit tax fraud. However, religiosity in taxpayers can be a factor that prevents tax fraud from occurring.